AKR1C1 protects against intracerebral hemorrhage by suppressing neuronal cell death via the P53/SLC7A11/GPX4 axis - Qiyu Yang; Chunyan Wang; Jingwei Cao; Zhanbin Tang; Shurong Duan (Brain Research Bulletin)
Intracerebral hemorrhage (ICH) is associated with the highest rates of mortality and residual disability. To date, effective treatments to delay or prevent ICH are still lacking. Multiple forms of neuronal cell death have been discovered following ICH, including apoptosis, necrosis, autophagy, and ferroptosis. Aldo-keto reductase family 1 member C1 (AKR1C1) has been identified to act as a protective factor in ferroptosis. However, whether AKR1C1 was involved in the development of ICH was unknown. In this study, the left cerebral striatum of the Sprague-Dawley rat was injected with collagenase type IV to induce an in vivo model. Primary rat cortical neurons treated with oxygen hemoglobin (OxyHb) were applied to as an in vitro model. AKR1C1 was found to be downregulated and immunoreactivity colocalized with NeuN-positive neurons in the perihematomal region. Rats injected with lentiviral particles overexpressing AKR1C1 showed the reduction of cerebral hematoma and the remission of blood-brain barrier disruption. Moreover, AKR1C1 upregulation repressed cell apoptosis and ferroptosis induced by ICH through downregulating the expression of pro-apoptotic factors, inhibiting iron accumulation and lipid peroxidation, along with increasing the expression of solute carrier family 7 member 11 (SLC7A11) and glutathione peroxidase 4 (GPX4). The results of in vitro assays were consistent with results from the in vivo. Mechanistically, P53 overexpression augmented the cellular damage in OxyHb-stimulated neurons when AKR1C1 was overexpressed. Taken together, AKR1C1 improves ICH injury by inhibiting neuronal cell death via negatively regulating P53 expression and affecting the SLC7A11/GPX4 pathway.